Synthesis and physical-chemical properties of 3-(4-(tert-butyl)phenyl)-5-(R-ylthio)-4H-1,2,4-triazol-4-amines - I. I. Aksyonova; O. I. Panasenko; Ye. G. Knysh (Zaporozhye State Medical University, 2016)
Aim. 1,2,4-triazole derivatives are widely used in medical practice due to its wide range of biological effect and small toxicity. This fact makes this class of organic heterocyclic compounds especially interesting and promising for the study of their physical-chemical and biological properties. Thirteen novel compounds, namely 3-(4- (tert-butyl)phenyl)-5-(R-ylthio)-4H-1,2,4-triazole-4-amines, that were not previously described in the literature, have been synthesized with the aim of search for new potentially biologically active compounds. Methods and results. In order to create new biologically active compounds 13 novel 3-(4-(tert-butyl)phenyl)-5-(R-ylthio)-4H-1,2,4-triazole-4-amines have been synthesized, preparative methods of their synthesis have been proposed, the structure of synthesized compounds has been confirmed by IR-, 1H NMR-spectroscopy, chromatography-mass spectrometry and elemental analysis. In addition, the compounds have been tested for antimicrobial and antioxidative activities. Conclusions. A preparative methods of synthesis of 3-(4-(tert-butyl)phenyl)-5-(R-ylthio)-4H-1,2,4-triazol-4-amines that can be used for chemical modeling of new biologically active compounds are described. The structure of the synthesized compounds was confirmed by complex of modern methods of investigation, namely: IR-, 1H NMR-spectroscopy, chromatography-mass spectrometry and element analysis. This indicates the possibility of using these substances to further biological studies.